2015
DOI: 10.1371/journal.pone.0132206
|View full text |Cite
|
Sign up to set email alerts
|

Community Perceptions on Integrating Animal Vaccination and Health Education by Veterinary and Public Health Workers in the Prevention of Brucellosis among Pastoral Communities of South Western Uganda

Abstract: BackgroundBrucellosis is a zoonotic disease of veterinary, public health, and economic significance in most developing countries, yet there are few studies that show integrated human and veterinary health care intervention focusing on integration at both activity and actors levels. The aim of our study, therefore, was to explore community perceptions on integration of animal vaccination and health education by veterinary and public health workers in the management of brucellosis in Uganda.MethodsThis study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…This approach was highly regarded among the community and saved costs and time (Lankester et al 2019). In Uganda, the integration of vaccination and health education to combat brucellosis was perceived by pastoralists and health service providers as feasible and desirable (Kansiime et al 2015). In addition, mobile clinics are a more suitable method of service delivery for pastoralists and often more cost-effective, as they mirror their nomadic lifestyle (El Shiekh and van der Kwaak 2015; Weibel et al 2008;Mocellin and Foggin 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was highly regarded among the community and saved costs and time (Lankester et al 2019). In Uganda, the integration of vaccination and health education to combat brucellosis was perceived by pastoralists and health service providers as feasible and desirable (Kansiime et al 2015). In addition, mobile clinics are a more suitable method of service delivery for pastoralists and often more cost-effective, as they mirror their nomadic lifestyle (El Shiekh and van der Kwaak 2015; Weibel et al 2008;Mocellin and Foggin 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, integrated, mobile service delivery can improve pastoralist health. In order to implement this approach, new coordination mechanisms and health system infrastructure in ASALs is needed (Kansiime et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of education on brucellosis prevention among livestock breeders is studied through some researches [12,15,[36][37][38][39]. However, the effectiveness of education in those researches is evaluated by researcher-made questionnaires and the psychometric properties of research questionnaires in those researches are not reported.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, awareness was the most predictive construct of livestock breeder preventive behavior of livestock breeder. The role of awareness and attitude in changing health behaviors is highlighted in studies [12,15,40]. For instance, in one study livestock breeders' attitude and practice scores were signi cantly improved after a PRECEDE-based educational intervention in a quasiexperimental study [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation